PENYUSUNAN PEDOMAN PENGELOLAAN KEUANGAN PESANTREN - Maskuri Maskuri (LP2M Universitas Ibrahimy, 2020)
Islamic boarding schools inevitably provide services for the implementation and management processes. It requires adjustments to increasing needs. Each Islamic boarding school has different characteristics, because It is founded by different figures. There are different ways to financial management in Islamic boarding schools. The role of Kiai as a central figure is very decisive in financial management. Pondok Pesantren Salafiyah Syafi'iyah Sukorejo is one of the Islamic boarding schools that have own financial management system. Three units are technically managing finances in Pondok Pesantren Salafiyah Syafi'iyah Sukorejo. They are Treasurer, the Supreme Audit and Wealth Agency of Ma'had (BPK2M), and the Budget Team. To ensure the service system in financial management, it is necessary to develop financial management guidelines. The mentoring steps taken included sharing ideas, absorbing information, discussing and conducting joint studies with stakeholders in the Islamic boarding schools. As a result, the draft financial management guidelines were included in the master plan for Islamic boarding schools. The need for guidance on financial management of Islamic boarding schools is in line with the theory of planning, innovation, and several financial regulations established by the State. In management, planning is needed because the spirit is innovation and meeting the demands of change to meet the needs of the organizers and the Islamic boarding schools community itself.